2016
DOI: 10.1007/s00586-016-4662-6
|View full text |Cite
|
Sign up to set email alerts
|

Another diagnostic tool in thoracolumbar posterior ligament complex injury: interspinous distance ratio

Abstract: In this study, in cases where it was difficult to make a diagnosis of the injury in the posterior ligament complex, based on the interspinous distance ratio (ISDR) of 120 % measured in plain X-ray in a lateral decubitus position, the sensitivity was 81.3 %, the specificity was 76.2 %, and the accuracy was 79.2 %. Therefore, measuring the ISDR will be helpful in determining whether surgical treatment is required in patients with thoracolumbar injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to the result, if ISD increases, the incidence of PLC injury increases. Therefore, it can be considered as a significant parameter in the diagnosis of PLC injury [27, 32,33].…”
Section: Discussionmentioning
confidence: 99%
“…According to the result, if ISD increases, the incidence of PLC injury increases. Therefore, it can be considered as a significant parameter in the diagnosis of PLC injury [27, 32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies (5)(6)(7) have reported that LOVBH is not associated with PLC or disc injuries. However, it should be noted that these studies either excluded osteoporotic fractures (7,8) or confused them with non-osteoporotic fractures (5,9) when investigating the relationship between LOVBH and PLC injuries. The bone mass of different vertebrae varies, especially between osteoporotic and non-osteoporotic vertebrae.…”
Section: Introductionmentioning
confidence: 99%